Analysis of antimicrobial resistance and clinical features of Staphylococcus aureus-infected bone and joint infections in children - Xingguang Chen; Ting Zhuang; Chengda Zou; Yao Liu; Qian Sun; Mengxia Li; Wen Zheng; Chaochen Zhao; Xiaodong Wang (BMC Pediatrics)
Abstract Objective This study investigates the antimicrobial resistance and clinical features of Staphylococcus aureus (S. aureus) in bone and joint infections (BJIs) among children under 14 years old, providing insights for optimal antibiotic usage. Methods A retrospective analysis was conducted on the clinical data from children treated for BJIs at the Children’s Hospital of Soochow University between January 2019 to December 2023. Bacterial cultures were examined, focusing on S. aureus. Clinical features of children with methicillin-sensitive Staphylococcus aureus (MSSA) and methicillin-resistant Staphylococcus aureus (MRSA) infections were compared. Results Among the 110 cases of culture-positive BJIs, 116 pathogenic strains were identified, with, S. aureus being the most prevalent (75.00%, 87/116). No resistance to quinupristin/dalfopristin, linezolid, vancomycin, tigecycline, rifampin or teicoplanin was detected. The resistance rate to penicillin was 90.80% (79/87), while resistance rates to clindamycin and erythromycin were 37.93% (33/87) and 36.78% (32/87), respectively. MRSA accounted for 28.74% (25/87) of S. aureus isolates. There were no significant differences in gender, age, infection site, clinical symptoms, laboratory indicators, hospital stay, or surgical intervention between MSSA and MRSA groups (p > 0.05). However, patients with positive X-ray findings were more likely to have MRSA infections (p = 0.033). Subgroup analysis revealed that children older than 48 months with positive X-ray results were more likely to have MRSA (p = 0.048). Conclusion In China, S. aureus remains the predominant pathogen in children under 14 years old with BJIs. Among children older than 48 months, nearly one-third of BJIs are caused by MRSA, and positive X-ray findings may indicate a higher likelihood of MRSA in this age group. Further studies are required to validate these findings before they can be widely applied. Clinical trial number Not applicable.